Mechanical Characteristics and Correlation Analysis of Crack Propagation and Slip Cracking in Asphalt Pavement Surface Layer - Zhenyu, Yin (European Journal of Computational Mechanics, 2023)
With the rapid development in the field of road traffic, the problems of slip cracking and U-shaped cracks on the surface of asphalt pavement are becoming more and more prominent, which seriously affect the safety and service life of roads. In order to solve this problem, a reliable asphalt pavement model is established in this study by combining the joint simulation and secondary development of experimental test parameters. The model can accurately simulate the slip cracking of asphalt pavements under different conditions and provide detailed parametric analysis of the factors affecting crack development. The results show that the inter-ply bond damage no longer deteriorates when the inter-ply strength is 0.3 MPa, indicating that the form of inter-ply contact plays a role in controlling the development of slip cracks. In addition, the maximum interlayer shear stress increased by 21.1% during the increase of vehicle axle load from 100 kN to 200 kN on the asphalt pavement, which led to an increase in the length of slip cracks. Meanwhile, the maximum longitudinal tensile stress in the asphalt pavement surface layer increased by 10.2% and the maximum shear stress increased by 18.3% when the elastic modulus of the asphalt pavement surface layer was increased from 7500 MPa to 14500 MPa.